Index Penulis - Index Penulis TIP (Jurnal Teknologi Industri Pertanian, 2014)
INDEKS PENULIS VOLUME 24   Aman, W.P.                                                            137 Anandito, R.B.K.                                                      53 Andarwulan, N.                                                      209 Andasuryani                                                             43 Aryanto, A.Y.                                                           97   Bahmid, N.A.                                                         226 Bantacut, T.                                                            105 Budiastra, I.W.                                                         43   Damanyanthi, E.                                                       28 Darmanto, W.                                                         105 Daryanto, A.                                                           114 Dwiyanti, H.                                                             28 Dwiyono, K.                                                           179   Eriyatno                                                                    34   Fahma, F.                                                                125 Fahrizal                                                                   189   Gumbira-Sa’id, E.                                    11, 114, 157   Haditjaroko, L.                                                 20, 179 Hariyadi, P.                                                             209 Hasan, M.F.                                                            114 Hasanudin, U.                                                           11 Hendra                                                                      82 Herdiyeni, Y.                                                            82 Hermawan, D.                                                        125   Indrasti, N.S.                                                     97, 243 Ismayana, A.                                                          243   Jading, A.                                                                137 Jaya, R.                                                                     61   Kartika, I.A.                                                            125 Ketaren, S.                                                              148 Khasanah, L.U.                                                         53 Kurniati, M.                                                            125 Kusmana, C.                                                           200 Kustiyo, A.                                                                 1 Lubis, M.R.R.                                                           72 Machfud                                                     34, 61, 157 Maddu, A.                                                             226, 243 Mangunwidjaja, Dj.                                                218 Manurung, A.J.                                                         20 Marimin                                                      61, 82, 189 Meryandini, A.                                                         20 Mu’tamar, M.F.F.                                                     34   Pari, G.                                                                           157 Payung, P.                                                                     137 Purnomo, E.H.                                                        209 Purwanto, M.Y.J.                                                   189 Purwanto, Y.A.                                                        43   Raharja, S.                                                        61, 251 Richana, N.                                                            218 Rimbawan                                                               28 Riyadi, H.                                                                28 Romli, M.                                                                97 Rosmeika                                                               235   Sarono                                                                      11 Sartika, N.D.                                                           157 Sarungallo, Z.L.                                                      209 Setyaningsih, D.                                                     148 Sirait, K.E.                                                              251 Siregar, H.H.                                                               1 Slamet, A.S                                                                 1 Soewardi, K.                                                             34 Subiyantoro                                                            243 Sukmawati, L.                                                        148 Sulaeman, A.                                                            28 Sumaryanto                                                            189 Sunarti, T.C.                                  125, 157, 179,  218 Suparno, O.                                                      11, 179 Suprihatin                                             11, 72, 97, 243 Suryadarma, P.                                                       251 Suryani, A.                                                       72, 200 Suwandhi, I.                                                            200 Syamsu, K.                                               20, 125, 226   Tambunan, A.H.                                                     235 Tethool, E.F.                                                           137 Tiryana, T.                                                              200   Utami, R.                                                                  53   Waningsih, M.                                                          53 Warsiki, E.                                                              166 Winarti, C.                                                              218 Wulandari, N.                                                         166   Yani, M.                                                          166, 189 Yoyo, T.                                                                  114 Yuwono, A.S.                                                         235